Structural behaviour of aluminium self-piercing riveted joints: An experimental and numerical investigation - Hoang, N.-H.; Hanssen, A.-G.; Langseth, M.; Porcaro, R. (International journal of solids and structures, 2012)
The present paper deals with the structural behaviour of self-piercing riveted joints based on aluminium and steel rivets. Two T-components made of two open aluminium profiles in alloy AA6063 temper T4 joined by 6 and 12 rivets, respectively, were designed and tested under quasi-static loading conditions. A new test device was designed to perform the tests of the T-components under two different load cases. Experimental results of the T-components joined by using aluminium self-piercing rivets were then compared with the corresponding components joined by using steel rivets in terms of force-displacement curves, deformation modes of the components as well as rivet failure modes. Further, the experimental results of the T-components based on aluminium rivets were used to validate a resultant-based point-connector model for self-piercing rivets proposed by Hanssen et al. (2010) using shell elements.